The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.22312/sdusbed.295022
|View full text |Cite
|
Sign up to set email alerts
|

Pediatri Kliniklerinde Çalışan Hemşirelerin Hasta Güvenliği İle İlgili Sık Karşılaştıkları Sorunlar

Abstract: Health institutions are different places for the paediatric patients and they provide an environment which restrains them from their everyday lives and roles for a certain time. The researchers report that the children need a care and treatment different than adults. Children are not miniature adults. In comparison to adults, they face more serious consequences when they are exposed to a medical faults or damage due to their physical, cognitive, emotional and anatomical incapability. In this regard, paediatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Children receiving care in the pediatric intensive care unit are vulnerable and depend on nurses to meet their needs. Pediatric nurses can assess children's care needs holistically, with a care plan developed in accordance with the principles of atraumatic and family-centered care (16,17). In Mattsson et al's (2013) qualitative study of nurses' concerns in PICU, it was found that nursing care was not always responsive to the child's needs and compromised the child's well-being (18).…”
Section: Discussionmentioning
confidence: 99%
“…Children receiving care in the pediatric intensive care unit are vulnerable and depend on nurses to meet their needs. Pediatric nurses can assess children's care needs holistically, with a care plan developed in accordance with the principles of atraumatic and family-centered care (16,17). In Mattsson et al's (2013) qualitative study of nurses' concerns in PICU, it was found that nursing care was not always responsive to the child's needs and compromised the child's well-being (18).…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric outpatient clinics are generally very busy polyclinics. This situation can cause stressful communication in the waiting area (Pazarcıkcı and Efe, 2018). It is necessary to wait for a long time to take and wait for the examination.…”
Section: Discussionmentioning
confidence: 99%